Photodissociation dynamics of methyl iodide across the A-band probed by femtosecond extreme ultraviolet photoelectron spectroscopy. (5th August 2021) - Downes-Ward, Briony; Warne, Emily M; Woodhouse, Joanne; Parkes, Michael A; Springate, Emma; Pearcy, Philip A J; Zhang, Yu; Karras, Gabriel; Wyatt, Adam S; Chapman, Richard T; Minns, Russell S
Abstract: The dissociation dynamics of CH3 I at three UV pump wavelengths (279 nm, 254 nm, 243 nm) are measured using an extreme ultraviolet probe in a time-resolved photoelectron spectroscopy experiment. The results are compared with previously published data at a pump wavelength of 269 nm, [2020, Phys. Chem. Chem. Phys., 22, 25695], with complementary photoelectron spectroscopy experiments performed using a multiphoton ionization (MPI) probe [2019, Phys. Chem. Chem. Phys., 21, 11142] and with the recent action spectroscopy measurements of Murillo-Sánchez et al [2020, J. Chem. Phys., 152, 014304]. The measurements at 279 nm and 243 nm show signals that are consistent with rapid dissociation along the C–I bond occurring on timescales that are consistent with previous measurements. The measurements at 254 nm show a significantly longer excited state lifetime with a secondary feature appearing after 100 fs which is indicative of more complex dynamics in the excited state. The time-dependence of the changes are consistent with the previously measured MPI photoelectron spectroscopy measurements of Warne et al, [2019, Phys. Chem. Chem. Phys., 21, 11142]. The consistency of the signal appearance across ionization processes suggests that the extended observation time at 254 nm is not an artefact of the previously used MPI process but is caused by more complex dynamics on the excited state potential. Whether this is caused by complex vibrational dynamics on the dominant 3 Q 0 state or is due to enhanced population and dynamics on the 1 Q 1 state remains an open question.